2020
DOI: 10.1002/jmv.26759
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of HBV and HCV in female sex workers from four cities in the state of Pará, northern Brazil

Abstract: Female sex workers (FSWs) represent a high vulnerability group for the acquisition of sexual and parenteral infections such as hepatitis B virus (HBV) and hepatitis C virus (HCV) infections. The present study aimed to determine the prevalence of serological markers and risk factors associated with exposure to HBV and HCV among FSWs in the state of Pará, Brazil. A cross‐sectional study using principles of the time location sampling (TLS) method was conducted in four cities (Belém, Bragança, Barcarena, and Augus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…As a main preventive measure, HBV vaccination should be extended to high-risk groups. Although an HBV vaccination program has been developed in the Amazon region in recent decades [ 14 , 20 ], epidemiological studies have indicated very low vaccine coverage in PWUDs and FSWs in this area, thus indicating the urgent need to vaccinate members of these vulnerable groups [ 13 , 37 , 66 , 98 ]. The neglect of this preventive measure contributes to the maintenance of HBV circulation on a larger scale in these high-risk groups and may contribute to the emergence of new infections, co-infections, and mutations in the genome, such as those recorded in this study.…”
Section: Discussionmentioning
confidence: 99%
“…As a main preventive measure, HBV vaccination should be extended to high-risk groups. Although an HBV vaccination program has been developed in the Amazon region in recent decades [ 14 , 20 ], epidemiological studies have indicated very low vaccine coverage in PWUDs and FSWs in this area, thus indicating the urgent need to vaccinate members of these vulnerable groups [ 13 , 37 , 66 , 98 ]. The neglect of this preventive measure contributes to the maintenance of HBV circulation on a larger scale in these high-risk groups and may contribute to the emergence of new infections, co-infections, and mutations in the genome, such as those recorded in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of vaccine immunity (anti-HBs only) ranged from 0.7% to 4.7% [ 141 , 142 ] and genotype A (69.0%) was the predominant one [ 143 ]. Reduced monthly income, low education, unprotected sex, multiple sexual partners, unsafe sexual practices, illicit drug use and co-infection with other STIs have been associated with exposure to HBV [ 141 , 143 ]. These findings indicate the need for urgent measures to control the spread of HBV and other STIs and to promote the health of FSWs.…”
Section: Hbv: the Impact Of The Geographical Area On The Prevalence Of The Virus In The Brazilian Amazonmentioning
confidence: 99%
“…Epidemiological investigations among high-risk groups (FSWs and PWUD) showed prevalence rates of HBV infection ranging from 3.0% to 13.7% among FSWs that offered their services in municipalities and riverside communities in the state of Pará [121,141]. The rate of vaccine immunity (anti-HBs only) ranged from 0.7% to 4.7% [141,142] and genotype A (69.0%) was the predominant one [143].…”
Section: Hbv: the Impact Of The Geographical Area On The Prevalence Of The Virus In The Brazilian Amazonmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Alliance against Viral Hepatitis and WHO currently promote strategies to eliminate viral hepatitis as a public health problem, to reduce new cases by 90% and deaths from viral hepatitis by 65% by 2030 [ 11 ]. On the other hand, to achieve these goals, it is essential to reach socially vulnerable subpopulations at risk of exposure to HBV and HCV [ 12 , 13 ], such as immigrants and refugees, an emerging population worldwide.…”
Section: Introductionmentioning
confidence: 99%